2014
DOI: 10.1210/jc.2013-3686
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Levothyroxine Replacement or Suppressive Therapy on Health Status, Mood, and Cognition

Abstract: Women receiving TSH-suppressive doses of L-T4 do not have central nervous system dysfunction due to exogenous subclinical thyrotoxicosis, but TSH-suppressed and L-T4-replaced women have slight decrements in health status and mood that may be related to self-knowledge of the presence of a thyroid condition or other uncharacterized factors. These mood alterations do not impair cognitive function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…Two of them are sensitive measures of working memory (N-Back and Subject Ordered Pointing) (42,43). In concordance with the few available reports in non-LT4 treated (7,17) and LT4 treated euthyroid subjects (23,26,27), we did not find associations between thyroid function and these four measures.…”
supporting
confidence: 92%
See 4 more Smart Citations
“…Two of them are sensitive measures of working memory (N-Back and Subject Ordered Pointing) (42,43). In concordance with the few available reports in non-LT4 treated (7,17) and LT4 treated euthyroid subjects (23,26,27), we did not find associations between thyroid function and these four measures.…”
supporting
confidence: 92%
“…Some studies have shown that LT4 treated subjects have decreased psychological well-being or cognitive measures compared with control groups, while other studies have reported no differences in these measures (11,(22)(23)(24)(25)(26)(27). Only four studies further investigated whether outcomes varied by TSH or thyroid hormone levels within the reference range in LT4 treated subjects, again with divergent findings (11,23,25,27).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations